Are Turkish EFL pre-service teachers ready to manage intercultural challenges?. Issue 2 (4th March 2018) - Genç, Gülten
Abstract: English as a foreign language (EFL) teachers, as the backbone of language teaching system, are expected to raise the awareness level of students' intercultural communication competence by helping them relate their own culture to foreign cultures, empathise with foreign cultures' perspectives and tolerate the ambiguities or differences. This study examines the relationship between certain personal factors such as age, gender, year of study, overseas experience and students' preferences for Turkish movies over foreign ones and three predictors of intercultural communication competence namely, ambiguity tolerance, empathy and open-mindedness. The sample group of the study consisted of 145 prospective English teachers in the Educational Faculty of a state university in Turkey. The participants were asked to fill out a questionnaire consisting of two parts which investigated their background and perceived levels of ambiguity tolerance, open-mindedness and empathy in Turkish EFL context. The results indicated that half of pre-service EFL teachers had poor intercultural communication competence. In particular, males, the final-year students and those who had been abroad indicated higher levels of tolerance than their respective counterparts. Besides, age and students' preferences for Turkish or foreign movies were not significant factors in any of the predictors of intercultural communication competence.